TAFSIR KONTEKSTUAL ABDULLAH SAEED DALAM QS. ĀLI ‘IMRĀN [3]:161 DAN QS. AL-MĀ’IDAH [5]: 42 TENTANG KORUPSI - Wildan (Academic Journal of Islamic Principles and Philosophy, 2025)
Corruption is a serious problem that undermines the social, political, and moral order of society, including in Indonesia. While the term “corruption” is not explicitly mentioned in the Quran, several terms, such as “gulul” (betrayal of a trust) and “as-suḥt” (bribery/illicit wealth), are closely related to corrupt practices. This study aims to analyze the verses of the Qur'an related to this phenomenon, especially QS. Āli ‘Imrān [3]: 161 and QS. al-Mā’idah [5]: 42, through Abdullah Saeed's contextual interpretation approach. The research method used is library research with primary sources in the form of the Qur'an and the works of Abdullah Saeed, as well as secondary sources in the form of classical interpretations, contemporary interpretations, and previous research that discusses the issue of corruption from an Islamic perspective. The results of the study show that classical to modern exegetes such as al-Ṭabarī, al-Qurṭubī, as-Shabuni and others interpret gulûl as betrayal in the distribution of war booty and as-suḥt as a form of bribery that undermines legal justice. Through a contextual approach, Abdullah Saeed expands the meaning of these two terms to make them relevant to contemporary corruption issues, namely all forms of abuse of public trust, embezzlement of assets, and bribery practices within the modern legal and bureaucratic systems. Thus, this study confirms that the Qur'an not only provides a moral prohibition against corrupt practices but also offers applicable social ethical principles to support corruption eradication in the modern era.